Association of community cancer centers key quality care recommendations for stage IB to IIIA non–small cell lung cancer. Issue 28 (1st October 2022) - Smeltzer, Matthew; Stiles, Brendon Matthew; Lee, Percy; Kim, Joseph; Lile, Ashley; Megally, Sandra; Boehmer, Leigh
Abstract : 30 Background: Early-stage diagnosis of non-small cell lung cancer (NSCLC) provides patients the best opportunity for long-term survival. There are documented deficiencies, however, in the quality of care many receive. Optimal care for persons with early-stage NSCLC requires a well-coordinated, multifaceted approach. The Association of Community Cancer Centers (ACCC) assembled a group of experts to create a quality document to guide care for persons with early-stage NSCLC. Methods: We convened an expert panel of lung cancer specialists with expertise in medical oncology, thoracic surgery, radiation oncology, oncology nursing, and epidemiology. The panel developed a document with 30 key quality recommendations for care of persons with stage IB to IIIA NSCLC. Evidence-based recommendations were incorporated from American Society of Clinical Oncology, International Association for the Study of Lung Cancer, American Society for Radiation Oncology, Commission on Cancer, and National Comprehensive Cancer Network guidelines and recommendations. A consensus decision-making model was utilized and recommendations were compiled in tabular format. Results: The key areas identified by the committee were: Care Coordination and Patient Education, Diagnosis and Biomarker Testing, Staging and Treatment Planning, and Post-Treatment Survivorship Care. Highlights of Care Coordination and Patient Education included shared decision-making, access to a care navigator, psychosocial support and patient education on NSCLC management, clinical trials, smoking cessation and tobacco dependence interventions, and community resources. Diagnosis and Biomarker Testing recommendations include multidisciplinary evaluation and care coordination, biomarker testing (eg, EGFR) in patients with stage IB to IIIA NSCLC who may be eligible for targeted therapy, PD-L1 testing in patients with resected stage II to IIIA NSCLC, and discussing post-resection targeted therapy. Staging and Treatment Planning recommendations include invasive staging, multimodality staging as appropriate, multidisciplinary treatment planning, and post-resection initiation of adjuvant therapy within 60 days when given. Recommendations for Post-Treatment Survivorship Care include implementation of standard surveillance, survivorship care plans, access to palliative care services, and sustained assessment of distress and referral to psychosocial support services. Conclusions: Well-coordinated, evidence-based care delivery is paramount to achieving the best outcome for individuals with early-stage NSCLC. The ACCC quality care document is an expert designed tool, combining evidence-based recommendations from multiple sources, to help achieve this goal.